Approaches Towards Femicides on Social Media in Turkey: A Sociological Analysis - Erjem, Yaşar (Journal of Applied And Theoretical Social Sciences, 2024)
The subject of this study is femicide in Turkey. Femicide has gradually increased in Turkey in the last 25 years and has become an important social problem on the country's agenda. Femicide is also an important study topic in social sciences. It is observed that a descriptive analysis of limited information about the murder is made, mostly based on newspaper and internet news in related studies. It is seen that the opinions and approaches of the society about this important problem are not systematically examined. This study aims to learn the causes, effects, solution, views and approaches of the society towards the perpetrators and victims of femicides. The study aims to explain and understand these dimensions expressed about the murders. The research was designed on the basis of the qualitative research paradigm. The data of the research consists of 1100 comments on 20 femicides on the popular social media platform Facebook. The data obtained from Facebook were categorized and interpreted by content analysis. In conclusion, it has been revealed that society mostly described femicides with a female-oriented and legal approach, and also considers factors related to family, education, politics, religion and culture as important. While society generally considers the victim (woman) as pure, clean and innocent in femicides, it depicts the perpetrator (man) as bad and dangerous. The reaction to femicides has religious, emotional, pessimistic and rational dimensions. In the solution of femicides, the general tendency is based on law and punishment.